Greenhouse irrigation system based on AIoT - Tariq Benahmed; Seddiki Noureddine; Benahmed Khelifa (Institute of Advanced Engineering and Science, 2026)
Agriculture is one of the biggest consumers of fresh water. Different types of irrigation systems are available and used in agricultural greenhouses. These irrigation systems are traditional, which do not allow for water savings and have very high maintenance costs. Smart irrigation in agricultural greenhouses is an innovative approach that contributes to a more efficient use of water in agriculture by optimizing available resources and promoting a more sustainable and profitable production. Through the use of smart technologies such as the artificial intelligence internet of things (AIoT), smart irrigation allows adjusting the amounts of water provided to the actual needs of plants, based on factors from sensors such as temperature, air and soil humidity, crop growth stages, plant conditions, and soil types. This helps to avoid water waste and reduce the risks of water stress for plants, while improving the quality and yield of crops. This article presents a smart irrigation solution in greenhouses whose results have been validated by an experimental prototype.